Challenges and Strategies in Using TikTok for Vocabulary Learning: EFL University Students’ Perceptions - Elyana Putri Jessica; Izzati Gemi Seinsiani (PROJECT (Professional Journal of English Education), 2026)
Vocabulary learning through TikTok offers authentic language exposure, but it comes with certain challenges. It is important to understand how students face these challenges and adopt effective strategies to enhance learning outcomes. This study aims to examine the challenges EFL students face and the strategies they use to overcome them for effective learning outcomes. This study uses a qualitative research approach. An open-ended questionnaire and semi-structured interviews were used to collect the data. The data was analyzed using a thematic analysis. The findings show that students encounter challenges with informal language such as slang,  abbreviations, and idioms. The platform provides limited explanation and context. Students have difficulties in following various speeds and accents, while also facing distractions and inconsistent content quality. This condition allows students to develop adaptive learning strategies, including seeking meaning from external sources and making use of features such as comments, replay, pause, and subtitles. Students reinforce their vocabulary through practice, note-taking, and repetition. Some students also rely on contextual clues for understanding. Those strategies demonstrate that students actively manage their learning in an unstructured environment. Indicates that students’ capability to develop and implement suitable learning strategies is essential to obtain effective learning on TikTok.